Concept analysis: Community-based postnatal care - Katekani J. Shirindza; Thivhulawi Malwela; Maria S. Maputle (AOSIS, 2023)
Background: Community-based postnatal care is a valuable resource in the provision of maternal and neonatal care, specifically outside the hospital environment. However, its application in maternal and neonatal care is not clearly documented in relation to the rendering of services by primary caregivers. Objectives: This study clarifies the concept of 'community-based postnatal care' by using the concept analysis method. Method: To analyse the concept, relevant literatures were reviewed and analysed using the Walker and Avant method, namely, selecting a concept, determining the purpose of analysis, identifying all uses of the concept, defining attributes, identifying a model case, identifying borderline, related and contrary cases, identifying antecedents and consequences and identifying the empirical referents. Characteristics that repeatedly appeared throughout the literature were noted and categorised. Results: It was established from the concept analysis that 'community-based postnatal care' was complex and experienced ethnically. The analysis included that primary caregiver participation was based on home-levelled-skilled care, community participation and mobilisation, linkages of health services and community stakeholders. The attributes were influenced by antecedents and consequences. Conclusion: The empirical referents of community based can be integrated within the midwifery guidelines to measure the concept. When concepts are understood, self-care on early detection, early management and referral during early postnatal care will be enhanced. Contribution: The results of this study will foster independence, confidence and a respectful relationship between primary caregivers and the health care facility staff. The results are expected to guide future research and enhance community-based postnatal care in midwifery practice.